Cognitive Behavioral Anger Management for Man Transexuals in Prison a Group Study - Görgülü, Tuğba (The Bulletin of Legal Medicine, 2014)
Transsexuals who have been rejected because of their sexual orientations or exposed to sarcastic jokes or comments live a great deal of psychological and social problems such as anger and aggression. The feeling of stress comes from their being in a prison make these problems forcer they are living through. These stress elements cause transsexual individuals to have negative psychological consequences like crime behaviours. In the light of mentioned information, the aim of this group work is to provide anger management to those transsexuals who are in prison, help them to gain positive feelings and behaviours and minimise their maladaptive behaviours. In line with this purpose, an Anger Management Program focused on Cognitive Behavioural Therapy (CBT) which was developed by General Directorate of Prisons in Ministry of Justice within the scope of modernization of justice and the project of prison reform have been applied on this study. The group work was carried out with three male transsexual prisoners who were in Ankara Penal Institution Campus between the dates 31.10.2011 and 31.12.2011. In this article it is submits about administer of Anger Management Programme, group process and assessments.  As a result of the group work, it was observed that Anger Management Programme was an useful one, the anger of transsexual individuals and the core beliefs which used to be reasons of their anger changed in a positive way and they have started to show positive behaviour changes. Key Words: transsexual; anger management; cognitive behavioural therapy; closed prison
Keywords: transsexual; anger management; cognitive behavioural therapy; closed prison